Psychosocial Risks in the Changing World of Work: Moving from the Risk Assessment Culture to the Management of Opportunities - Di Tecco, Cristina; Persechino, Benedetta; Iavicoli, Sergio (La Medicina del Lavoro, 2023)
Increased attention to psychosocial risks and their potential impacts on workers’ mental and physical health has flourished due to the changes taking place in the world of work. The changes in the world of work and the recent worldwide events have exacerbated the existing psychosocial risks and brought out new psychosocial risks to be considered for protecting workers’ health. This favors the opening up of national and international debate on prioritizing psychosocial risks at work at the policies, strategies, and actions level. This contribution highlights the critical issues to be addressed, the needs to be covered, and the opportunities for better and more effective OSH protection in the workplace. Starting from a definition of psychosocial risks and their potential impacts, we offer an overview of the most recent developments in policies and strategies and the contribution of research in this field over time. A critical reflection on emerging topics, main needs, and challenges for organizations and stakeholders is offered. This time of change poses great concerns but also offers a great opportunity of moving from a culture of assessment to a culture of psychosocial risk management for improving workers’ well-being, productivity, and health, where the risk assessment is an important step but not a point of arrival.